2006
DOI: 10.2527/2006.8461535x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concentrated separator by-product (desugared molasses) on intake, ruminal fermentation, digestion, and microbial efficiency in beef steers fed grass hay1

Abstract: Concentrated separator by-product (CSB) is produced when beet molasses goes through an industrial desugaring process. To investigate the nutritional value of CSB as a supplement for grass hay diets (12.5% CP; DM basis), 4 ruminally and duodenally cannulated beef steers (332 +/- 2.3 kg) were used in a 4 x 4 Latin square with a 2 x 2 factorial arrangement of treatments. Factors were intake level: ad libitum (AL) vs. restricted (RE; 1.25% of BW, DM basis) and dietary CSB addition (0 vs. 10%; DM basis). Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
1
20
3
Order By: Relevance
“…Our previous study (Cao et al 2009a; showed that silages with 30% TC had higher LA content, compared to those with RB and GTW. In addition, M is a food byproduct of sugar beet and sugarcane production, although M with high soluble carbohydrates is used as a major energy source for meat or milk production (Wang and Goetsch 1998;Araba et al 2002;Granzin and Dryden 2005;Shellito et al 2006;Sahoo and Walli 2008). LAB can increase the LA content of a silage (Cai 2001;Cai et al 2003), and was well used to prepare silage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study (Cao et al 2009a; showed that silages with 30% TC had higher LA content, compared to those with RB and GTW. In addition, M is a food byproduct of sugar beet and sugarcane production, although M with high soluble carbohydrates is used as a major energy source for meat or milk production (Wang and Goetsch 1998;Araba et al 2002;Granzin and Dryden 2005;Shellito et al 2006;Sahoo and Walli 2008). LAB can increase the LA content of a silage (Cai 2001;Cai et al 2003), and was well used to prepare silage.…”
Section: Discussionmentioning
confidence: 99%
“…M is a fermentable carbohydrate (Maiga and Schingoethe 1997) and many researchers (Alli et al 1984) have reported its successful use with grass silage. In addition, M is a food byproduct of sugar beet and sugarcane production, although M with high soluble carbohydrates is used as a major energy source for meat or milk production (Wang and Goetsch 1998;Araba et al 2002;Granzin and Dryden 2005;Shellito et al 2006;Sahoo and Walli 2008). Alli et al (1984) assessed the effects of M on the fermentation of chopped whole-plant Leucaena.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although there are some reports that adding molasses has no effect on DM digestibility (Granzin & Dryden 2005;Wang & Goetsch 1998), many more studies (Shellito et al, 2006;Sahoo & Walli 2008) have reported that diets with molasses have higher ruminal DM digestibility.…”
Section: In Vitro Dm Digestibility and Methane And Vfa Productionmentioning
confidence: 99%
“…Normal molasses has several commercial applications, for example, as carbon source for fermentation industry, as fertilizer, and as animal feed, and it has also been reported to be used for biogas production (Lo et al, 1991). DM has less economic value than normal molasses (Olbrich, 1963), but application as animal feed has also been reported (Shellito et al, 2006). In general, DM contains lower concentration of sugar and higher concentration of ions such as sodium and potassium, than normal molasses due to the desugaring process.…”
Section: Introductionmentioning
confidence: 96%